Toxicity Evaluation of Long-Term Topical Application of Recombinant Human Keratinocyte Growth Factor-2 Eye Drops on Macaca Fascicularis - Li, Le; Li, Lijia; Chen, Qi; Yang, Xuanxin; Hui, Qi; AL-Azzani, Hamdi; Huang, Yadong; Cai, Jianqiu; Wang, Xiaojie; Jin, Zi (Frontiers in Pharmacology, 2021)
Recombinant human keratinocyte growth factor-2 (rhKGF-2), an effective agent for the regeneration of epithelial tissue, was found to have great potential for use in treatments of corneal diseases that involve corneal epithelial defects. Furthermore, the safety of long-term and high-dose external use of KGF-2 eye drops in rabbits has been well established previously. The aim of this study is to determine the safe dose range and target organs for toxicity of rhKGF-2 eye drops in Macaca fascicularis (M. fascicularis). The M. fascicularis animals were administered with different doses of rhKGF-2 eye drops (125, 500, and 2000 μg/mL) for four consecutive weeks, followed by a two-week recovery period. No significant differences in weight, electrocardiogram characteristics, blood and urine indexes, pathology, and bone marrow cells were detected among the animals in different groups. The corneas of some animals in the middle- and high-dose groups showed fluorescence when stained with sodium fluorescein, and then the staining disappeared on days 28 and 42. Anti-rhKGF-2 antibodies were detected in a small number of animals in the high-dose group, and their level decreased after rhKGF-2 withdrawal. No neutralizing antibodies were detected. We conclude that topical application of rhKGF-2 eye drops is safe at the dosage of 125 or 500 μg/mL on the M. fascicularis. This study is of great significance for the future clinical transformation of rhKGF-2 eye drops.